Depictive and metric body size estimation in anorexia nervosa and bulimia nervosa: A systematic review and meta-analysis. (November 2017) - Mölbert, Simone Claire; Klein, Lukas; Thaler, Anne; Mohler, Betty J.; Brozzo, Chiara; Martus, Peter; Karnath, Hans-Otto; Zipfel, Stephan; Giel, Katrin Elisabeth
Abstract: A distorted representation of one's own body is a diagnostic criterion and core psychopathology of both anorexia nervosa (AN) and bulimia nervosa (BN). Despite recent technical advances in research, it is still unknown whether this body image disturbance is characterized by body dissatisfaction and a low ideal weight and/or includes a distorted perception or processing of body size. In this article, we provide an update and meta-analysis of 42 articles summarizing measures and results for body size estimation (BSE) from 926 individuals with AN, 536 individuals with BN and 1920 controls. We replicate findings that individuals with AN and BN overestimate their body size as compared to controls ( ES  = 0.63). Our meta-regression shows that metric methods (BSE by direct or indirect spatial measures) yield larger effect sizes than depictive methods (BSE by evaluating distorted pictures), and that effect sizes are larger for patients with BN than for patients with AN. To interpret these results, we suggest a revised theoretical framework for BSE that accounts for differences between depictive and metric BSE methods regarding the underlying body representations (conceptual vs. perceptual, implicit vs. explicit). We also discuss clinical implications and argue for the importance of multimethod approaches to investigate body image disturbance. Highlights: Patients with Anorexia Nervosa and Bulimia Nervosa over-estimate their body with ES = 0.63 The degree of overestimation is moderated by the assessment method and patient diagnosis. We suggest a revised framework for BSE that integrates neuroscientific findings with previous models of body representation. Within this framework, we provide a clinical interpretation of body size overestimation.